CARBON SILICON-CONTAINING COMPOSITE MATRIX FOR THE DEVELOPMENT OF ADVANCED BACTERICIDAL APPLICATION AGENTS IN SURGERY - Klipov, V.D.; Kononko І.V.; Boshytska, N.V.; Serhieiev, V.P.; Kononko, N.V. (Reports of the National Academy of Sciences of Ukraine, 2024)
The technology of obtaining carbon fiber composite matrix VVCCM with silicon dioxide content for medical purposes is developed and the algorithm of its production is described. The conditions of the main stages of the technological process of VVCCM manufacturing are established. The influence of structure-forming additive on the conditions of formation of sol and structurally bonded layer of silicon dioxide in the developed material has been investigated. The parameters of the porous structure were studied by the benzene vapor moisture absorption method. The microstructure of surface and near-surface layers containing silicon dioxide in the composite matrix samples was investigated using a scanning electron microscope Mira 3 LMU (“Tescan”, Czech Republic), which made it possible to determine the location of the silicon dioxide layer in the composite structure, as well as its individual surface inclusions. The phenomenon of silicon dioxide aggregation into finely dispersed fiber-like structures after 100% combustion of carbon component in the process of ash formation at T = 1073 K has been found. The shape and size of silicon dioxide particles as well as their surface morphology were determined. Using the method of energy dispersive X-ray analysis and analytical chemistry methods to determine the chemical composition of composite matrix samples, it is proved that mineral inclusions on the surface of carbon fiber composite matrix microfibers are represented by silicon and silicon dioxide particles. The novelty of the developed technology lies in the discovery of an additional structural component in the composition of VVCKM, which allows us to refer it to a new class of carbon composite materials. In the composite matrix of VVCCM obtained by us, healing and bactericidal properties can be provided due to the presence of SiO2 particles of 100—500 nm in the structure of the material, which are able to promote cellular regeneration of the wound surface and destroy bacterial cells. This will allow to use VVKKM as bactericidal application agents in the treatment of purulent and complicated bacterial lesions both in the field and in hospital surgery.